THE PROCES OF ESTABLISHING XENOCRACY IN BALKAN STATES DURING 19TH CENTURY (Heritage, 2022)
The beginning of the 19th century was marked by the awakening of national liberation movements in the Balkan peninsula. This process was initiate by the Serbian revolution at 1804. These events launched more rebellion movements in Balkan against the Ottoman Empire. The Eastern Question was interested by the great powers in Europe: Russia, Great Britain, Austria-Hungary and France. All this states wanted to have in their hands Eastern Question. One way to do these was to appoint rulers from domestic dynasties in foreign courts. In that way, the first monarch in Greece was from the Bavarian dynasty. Another one was from dynasty Schleswig-Holstein-Sonderburg-Glücksburg. In Romania was the rulers from the dynasty Hohenzollern-Sigmaringen. The Bulgarian monarch was from the Saxe-Coburg-Gotha family. In the beginning on their rule, this monarch was not so popular, because they were from foreign countries. However, after some time, most of them adapted to the domestic public and culture in country were they ruled. King George of Greece was ruled fifty years, Romanian king Carol ruled from the 1866. to the 1914, and Bulgarian monarch Ferdinand I was ruled 32 years. The first king of Greece Otto, represents a ruler who came to the throne in an ungrateful and difficult period. He was not popular because he had no children and also was not political adept. He is remembered as the king who loved Greek culture and wear the Greek national clothes to the death. Alexander Battenberg was the Bulgarian king who came in the throne with Russian help. Also like king Otto, Alexander was not political adept and his rule was short. These data show us that the process of xenocracy was successful after all.
Keywords: Xenocracy, Greece, Romania, Bulgaria, Otto I, George I, Carol I, Alexander of Battenberg, Ferdinand I